2015
DOI: 10.1111/dar.12358
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of alcohol use among adolescents attending school in Kerala, India

Abstract: Alcohol use among adolescents in India deserves greater attention than it has previously received, marked as it is by an early onset and associated with a range of negative mental health problems. [ Jaisoorya T S, Beena K V, Beena M, Ellangovan K, Jose D C, Thennarasu K, Benegal V. Prevalence and correlates of alcohol use among adolescents attending school in Kerala, India. Drug Alcohol Rev 2016;35:523-529].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
0
29
1
Order By: Relevance
“…A recent study conducted in Ernakulam in Kerala among school students reported 15% prevalence in the 12–19-year-age group [24]. …”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted in Ernakulam in Kerala among school students reported 15% prevalence in the 12–19-year-age group [24]. …”
Section: Introductionmentioning
confidence: 99%
“…6 A study done in Kerala has also found a higher estimate of 23.2% alcohol use in school going adolescent boys in Kerala. 15 Reddy and Biswas in a study in Bangalore had also found that the most common substance of use among adolescents was alcohol 28% and smoking was found only in 3%. 16 .…”
Section: Discussionmentioning
confidence: 92%
“…17,26 But studies by Singh et al (28%) and Jaisoorya et al (15%), report much higher rates of prevalence. 9,29 Stress has been linked with elevated blood pressure across many studies. While Cohen's perceived stress scale is a simple self-administered tool with a high validity and good sensitivity, there are many other tools available which have been used in the other studies.…”
Section: Discussionmentioning
confidence: 99%